Implementasi Strategi Pembelajaran Inkuiri dalam Meningkatkan Motivasi Belajar Siswa: Implementation of Inquiry-Based Learning Strategy to Enhance Students' Learning Motivation - Rustandi, Nandi (Risalah Kharisma, 2023)
The study examines the implementation of inquiry-based learning strategies to enhance students' learning motivation at SMP Islam Cijati Cicantayan. The primary issue addressed is the low student motivation in traditional learning settings, which hinders active participation and critical thinking. The research aims to evaluate the effectiveness of inquiry-based learning in fostering engagement, confidence, and academic achievement. Using a qualitative case study approach, data were collected through participatory observation, in-depth interviews, and documentation involving students, teachers, and parents. Findings indicate a significant improvement in students' motivation, evidenced by increased participation, deeper material comprehension, and enhanced critical thinking skills. However, challenges such as time constraints, resource limitations, and varying student abilities were identified. The study concludes that inquiry-based learning effectively boosts motivation by promoting active learning, though its success depends on adaptive implementation and adequate support. The implications suggest the need for teacher training and curriculum adjustments to optimize inquiry-based strategies in diverse educational contexts.